Cost-effectiveness of malaria diagnostic methods in sub-Saharan Africa in an era of combination therapy - Samuel Shillcutt; Chantal Morel; Catherine Goodman; Paul Coleman; David Bell; Christopher JM Whitty; A Mills (Bulletin of the World Health Organization, 2008)
OBJECTIVE: To evaluate the relative cost-effectiveness in different sub-Saharan African settings of presumptive treatment, field-standard microscopy and rapid diagnostic tests (RDTs) to diagnose malaria. METHODS: We used a decision tree model and probabilistic sensitivity analysis applied to outpatients presenting at rural health facilities with suspected malaria. Costs and effects encompassed those for both patients positive on RDT (assuming artemisinin-based combination therapy) and febrile patients negative on RDT (assuming antibiotic treatment). Interventions were defined as cost-effective if they were less costly and more effective or had an incremental cost per disability-adjusted life year averted of less than US$ 150. Data were drawn from published and unpublished sources, supplemented with expert opinion. FINDINGS: RDTs were cost-effective compared with presumptive treatment up to high prevalences of Plasmodium falciparum parasitaemia. Decision-makers can be at least 50% confident of this result below 81% malaria prevalence, and 95% confident below 62% prevalence, a level seldom exceeded in practice. RDTs were more than 50% likely to be cost-saving below 58% prevalence. Relative to microscopy, RDTs were more than 85% likely to be cost-effective across all prevalence levels, reflecting their expected better accuracy under real-life conditions. Results were robust to extensive sensitivity analysis. The cost-effectiveness of RDTs mainly reflected improved treatment and health outcomes for non-malarial febrile illness, plus savings in antimalarial drug costs. Results were dependent on the assumption that prescribers used test results to guide treatment decisions. CONCLUSION: RDTs have the potential to be cost-effective in most parts of sub-Saharan Africa. Appropriate management of malaria and non-malarial febrile illnesses is required to reap the full benefits of these tests.